(3bGfhfLjIs - (3GdLZejfj , eMehO Hf eMeO Hf YeQ, TQa GdOjf CHh Ydj,J (B618 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3agPG eNJUQ jTJed Ydi RHOI eG jLjH ESJMVGQg ef UfGYh GdWH s
(3BNQgG (B:s
(3hCeG GdMdh hGdYSd (B[ (3agh (B] (3eYjf Ydi GdgVe , hGdYLjfi ZdjX s
(3bWYI ef fSNI CNQis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B181 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B198s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B865 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B145 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1113s
Keywords: (3GdWHs